Mobile danger info system (MDIS) - Fatin Nur Afifah, Che Hazahar (2019)
Since the beginning of time, humankind has needed to confront danger that are not completely comprehended before he or she has left on a game-plan. Parents are very concerned about the safety of their children. So, being sensitive to the environment is very important to ensure their child's safety is guaranteed. Teenage children are the main pillars of the nation's development and modernization. They should be sensitive and cautious with unforeseen dangers that at any time may come. The main goal of this system to alert people about the danger that happened around them. This system will help local people to aware about recent danger. The other people who witnessed the incident allow to share the incident. Rapid Application Development (RAD) methodologies are selected to be used for the development of this project. The selected methodology use minimal planning in favor of rapid prototyping. RAD model is based on prototyping and iterative development with no specific planning involved. The life cycle consists of four phases, which are Requirements Planning, User Design, Construction, and Cutover. After development, The User Acceptance Test (UAT) is done, where actual software users test the software to make sure it can handle the required tasks in real-world scenarios, according to its specifications and implementations.